The Posterior Signaling Center Is an Important Microenvironment for Homeostasis of the Drosophila Lymph Gland - Luo, Fangzhou; Yu, Shichao; Jin, Li Hua (Frontiers in Cell and Developmental Biology, 2020)
Drosophila hematopoiesis is a necessary process from embryo to adulthood. There are two main stages in this process: the first stage occurs in the head mesoderm during the embryonic stage and the second in a specialized hematopoietic organ, the lymph gland, along the dorsal vessel during the larval stage. The lymph gland consists of paired lobes, which are distinct from the cortical zone (CZ) that contains mature hemocytes, a medullary zone (MZ) that contains hematopoietic progenitors and the posterior signaling center (PSC) that specifically expresses the early B-cell factor (EBF) transcription factor Collier (Col) and the HOX factor Antennapedia (Antp) to form a microenvironment similar to that of the mammalian bone marrow hematopoietic stem cell niche. The PSC plays a key role in regulating hematopoietic progenitor differentiation. Moreover, the PSC contributes to the cellular immune response to wasp parasitism triggered by elevated ROS levels. Two recent studies revealed that hematopoietic progenitor maintenance is directly regulated by Col expressed in the MZ and is independent of the PSC, challenging the traditional model. In this review, we summarize the regulatory networks of PSC cell proliferation and the controversial conversation about the regulation of hematopoietic progenitor differentiation by the PSC. In addition, we summarize the response of the PSC to wasp egg infection.